Mechanics of L-bending process for dual phase steel sheets - Boroujeni, Sahar (2013)
This work explores the mechanics of the sheet metal bending process using 1.2 mm-thick dual phase DP600 steel blanks .Bending process parameters were set with die radii of 3, 1.5 and 0.7 mm and die clearance of 1.2 mm .The applied punch speed is 5 mm/min. Finite element (FE) simulation of the L-bending process is performed assuming plane strain and plane stress conditions. The steel blank is modelled as an elastic, non-linear hardening material while the tool blank holder and die are assumed to behave as rigid bodies. All contact surfaces are assumed to be frictionless. Distribution and evolution of stresses and plastic strains clearing bending were quantified. Springback of L-bent sheet metal was measured and compared with predicted values. The L-bent sheet metal was subjected to subsequent loading effect of residual plastic strains on deformation response were established. In addition recent demands are increased for advanced crash performance, while it is affordable and lightweight which is why in this case not only bending but also subsequent loading which applied on the bended zone (where residual stress and strain appeared) has been studied.